Management of leaf spots in soybean cultivation with fungicides at zero application - Zamarian, André Sarabia; Konzen, Derli Antônio; Mattei, Danielle (Scientia Agraria Paranaensis, 2024)
Soybean (Glycine max) is one of the most important commodities in Brazil. The main factors limiting its production are diseases, with approximately 40 diseases identified in the country, caused by fungi, bacteria, nematodes, and viruses. Foliar spots are common at the beginning of soybean development, and since pathogens can be present from the beginning of cultivation, preventive management is employed with application in the vegetative phase, 30 days after sowing (zero application). This study aims to evaluate the effectiveness of different fungicides from the chemical groups triazoles, strobilurins, multisites, and biological control in controlling foliar spots through zero application. The methodology followed the recommendations of the Ministério da Agricultura, Pecuária e Abastecimento (MAPA-Brazil) according to Normative Instruction No. 13 of 2011, with a randomized block design, 7 treatments, and 5 replications, totaling 35 plots. The treatments, applied 30 days after sowing at the V3 phenological stage, included a control with no application, Bacillus amyloliquefaciens, Picoxystrobin + Ciproconazole, Chlorothalonil, Saccharomyces cerevisiae, Picoxystrobin + benzovindiflupyr, and Tebuconazole + Trifloxystrobin. Disease incidence and severity, live canopy coverage index, and productivity variables were evaluated. The results demonstrate that Picoxystrobin + Ciproconazole and S. cerevisiae were the most effective treatments in reducing foliar disease incidence and severity while enhancing canopy retention and yield. These findings reinforce the importance of integrating chemical and biological control strategies in early disease management, particularly through zero application, to optimize soybean health and productivity.